ERICA: age at menarche and its association with nutritional status - Bruna de Siqueira Barros; Maria Cristina Maria Caetano Kuschnir; Katia Vergetti Bloch; Thiago Luiz Nogueira da Silva (Brazilian Society of Pediatrics, 2019)
Objective: To estimate the mean age at menarche and its association with nutritional status in Brazilian adolescents. Methods: The study sample included female adolescents aged 12-17 who participated in a multicenter, school‐based, country‐wide, cross‐sectional study entitled The Study of Cardiovascular Risk in Adolescents (Estudo de Riscos Cardiovasculares em Adolescentes [ERICA]). Mean and median ages at menarche in Brazil were estimated. The association of age at menarche with sociodemographic data and nutritional status were described as means and their respective 95% confidence intervals. Survival analysis was used to assess the age at menarche according to nutritional status categories and the log‐rank test was used to compare the medians. Bivariate and multivariate analyses were performed using Cox regression to verify the association between menarche and other variables. Results: A total of 73,624 students were evaluated, comprising 40,803 girls, of whom 37,390 reported menarche at a mean age of 11.71 years and a median of 12.41 years. Median age at menarche was lower in overweight and obese girls (p < 0.001). The multivariate analysis showed that excess weight (HR = 1.28; 95% CI 1.21-1.36; p < 0.001) and studying in a private school (HR = 1.06; 95% CI 1.02-1.10; p = 0.003) were associated with menarche. Conclusions: This is a pioneering study in Brazil with national and regional representativeness to estimate the mean and the median age of occurrence of menarche. Adolescents with excess weight had an earlier menarche than their peers, even after adjustment for confounding factors. Resumo: Objetivo: Estimar a média de idade de ocorrência da menarca e sua associação com o estado nutricional em adolescentes brasileiras. Métodos: Foram avaliados dados de meninas com 12 a 17 anos a partir de um estudo seccional de base escolar, com representatividade nacional e macrorregional, o ERICA (Estudo de Riscos Cardiovasculares em Adolescentes). Foram estimadas média e mediana de idade de ocorrência da menarca no Brasil, pelo método recordatório. A associação da idade da menarca com dados sociodemográficos e estado nutricional foi descrita como médias e seus respectivos IC95%. Análise de sobrevida foi utilizada para explorar a idade da menarca segundo categorias de estado nutricional e teste logrank foi utilizado para comparação das medianas. Análises bivariada e multivariada foram realizadas por meio da regressão de Cox para verificar a associação entre menarca e demais variáveis. Resultados: Foram avaliados 73.624 estudantes, 40.803 meninas, das quais 37.390 referiram ter apresentado menarca, sendo a média da idade de ocorrência de 11,71 anos e a mediana de 12,41 anos. As medianas da idade de ocorrência da menarca foram menores naquelas com sobrepeso e obesidade (p < 0,001). A análise multivariada evidenciou que excesso de peso (HR = 1,28, IC95% 1,21‐1,36, p < 0,001) e estudar em escola privada (HR = 1,06, IC95% 1,02‐1,10, p = 0,003) estão associados à menarca. Conclusões: Este foi o primeiro estudo brasileiro com representatividade nacional a estimar a média de idade de ocorrência da menarca. As adolescentes com excesso de peso apresentaram menarca em idade inferior às demais, mesmo após ajuste.Full English text available from: www.revespcardiol.org/en Keywords: Menarche, Obesity, Adolescent, Palavras‐chave: Menarca, Obesidade, Adolescente